The case for AI authorship in copyright law - SAW, Cheng Lim (Institutional Knowledge at Singapore Management University, 2026)
Today, with generative AI, literary and artistic works can be created almost effortlessly. There is at present intense debate as to whether works generated by AI – broadly categorised as “AI-assisted” and “AI-generated” works – ought to attract copyright protection. AI-assisted works are those that involve some degree of human intervention. Where AI-generated works are concerned, however, such works are created autonomously by the AI itself with minimal (de minimis) input from an identifiable human being. Presently, it is generally accepted that AI-generated works do not attract copyright protection for want of a human author.This article examines whether it is possible to legally recognise AI authorship and whether copyright can, in appropriate circumstances, attach to AI-authored works. The authors are of the view that there are sound doctrinal and policy reasons for recognising AI authorship and that the law would be better served if it recognises the possibility of an AI author.Understandably, human authorship is a longstanding tenet in copyright law. The assumption that only humans can create and innovate will increasingly be challenged as AI marches on into the future. Rather than wait for the arrival of more advanced AI, it would be prescient for policy makers to effect appropriate legislative amendments to accommodate what would arguably become an eventual reality.